Colombo declaration on epidemiology in Southeast Asia - Vinod K Srivastava (Wolters Kluwer Medknow Publications, 2020)
The Colombo Declaration on Epidemiology in Southeast Asia is based on the deliberations by the delegates of the conference and representatives of the Regional Public Health/Epidemiology Associations held during the Southeast Asia Regional Group Meeting of International Epidemiological Association/College of Community Physicians of Sri Lanka at Colombo, Sri Lanka, on September 19-21, 2019.